MARJAMBAR AS A TRADITIONAL COMMUNICATION MEDIUM IN MAINTAINING INTERFAITH RELATIONSHIPS IN THE BUNG BONDAR SUBDISTRICT, SIPIROK DISTRICT, NORTH SUMATRA - Aulia, Rezki; Lubis, Suwardi; Zulkarnain , Iskandar; Kurniawati, Dewi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research aims to analyze the meaning of symbols in the implementation of marjambar as a traditional communication medium. Qualitative descriptive research methods were employed to gather data, utilizing techniques such as in-depth interviews, observation, and documentary studies. The results of the research indicate that the implementation of marjambar during religious festivals is interpreted as a form of tolerance among people of different religions, considering that the Batak Angkola community residing in Bunga Bondar is still bound by blood ties. The mandatory foods served during the implementation, namely dodol, lemang, and tuangan, carry the meaning of dalihan na tolu. In conclusion, the implementation of marjambar is capable of maintaining relationships among people of different religions. This is evidenced by the harmonious coexistence among followers of different religions, the absence of religious conflicts for centuries, collaborative efforts among residents in social life, and the presence of numerous closely related religious symbols